Use of Semantic Web Technologies for Meeting Management Software Development - Nikov, Aleksandar; Jovanovik, Milosh; Stojanov, Riste; Petkovski, Milan; Trajanov, Dimitar (Springer Berlin Heidelberg, 2009)
One of the major concerns about the process of developing and maintaining a meeting software application is the complexity and robustness of the architecture and the underlying data model. That sometimes creates a problem with the need of restructuring the interface or the business logic, due to changes in requirements. Therefore, we need a flexible architecture framework, one that will provide easy and fast model modification. In this paper we present our ongoing work for developing an online meeting application, which is based on a flexible architecture framework. The application development is based on the following concepts: a data model based on ontologies and semi-structured data stored in RDF format, a service oriented architecture with the capability of automatic composition of semantic web services, and a user interface based on a guided natural language input, dynamic forms, and a graphic data representation tool, both based on ontologies.
Keywords: semantic web, meeting software, architecture, ontologies, OWL, RDF